Evaluating the Performance of the Indonesian Civil Servants to Enhance Public Service Quality: A Normative Juridical Study - Syarifa Fizra Almahdaly; Andira Arfadisa Falya; Vicka Estu Putri Anugrah; Diandra Salsabila Faradiba (Institute of Multidisciplinary Research and Community Service, 2023)
Abstract: The Civil Servants plays a central role in improving the quality of public services in Indonesia, including the implementation of government policies, service facilitation, and responding to the needs of the community. This study aims to identify the role of Civil Servants in enhancing the quality of public services, the factors influencing Civil Servants performance, and its impact on public satisfaction. The research method used is a literature review with a descriptive analysis of regulations, Civil Servants professionalism principles, and obstacles encountered in task implementation. The results show that Civil Servants professionalism, including competence, responsibility, and integrity, significantly influences the effectiveness of public service delivery. Moreover, obstacles such as the lack of a measurable performance management system, unconstructive evaluations, and limited technology also affect Civil Servants performance. Strengthening the merit system, continuous training, and the application of principles of transparency and accountability in service delivery are necessary steps to improve Civil Servants performance. In conclusion, good Civil Servants performance will enhance the quality of public services and strengthen public trust in the government, thus supporting the achievement of national development goals. Keywords: state civil apparatus, public service quality, professionalism, merit system, performance barriers.